Impact of Gout on Left Atrial Function: A Prospective Speckle-Tracking Echocardiographic Study - Pan, Kuo-Li; Lin, Jing-Chi; Lin, Chun-Liang; Chen, Mien-Cheng; Chang, Shih-Tai; Chung, Chang-Min; Hsu, Jen-Te (PloS one, 2014)
The purpose of our study was to evaluate the left ventricular (LV) and left atrial (LA) function in patients with gout. A total of 173 patients underwent a comprehensive Doppler-echocardiography examination. Participants were divided into four groups-Stage 0: control (n = 35), Stage I: asymptomatic hyperuricemia (n = 30), Stage II: gouty arthritis without tophi (n = 58), and Stage III: tophaceous gout (n = 50). Serum uric acid levels were not significantly different between stage I, II and III. Stage III patients demonstrated a higher ratio of the transmitral and myocardial peak early diastolic velocities (E/Em) (10.50 ± 3.18 vs. 8.58 ± 2.07; P = 0.008), and larger maximal LA volume index (LAVi) (29.60 ± 9.89 vs. 20.07 ± 4.76 ml/m(2); P<0.001) compared with controls. Stage III patients had decreased LV global longitudinal systolic strain (LVε) compared with controls (-20.2 ± 3.06 vs. -21.79 ± 2.27; P = 0.002). Stage III patients also had decreased peak atrial longitudinal strain rate during ventricular systole (ALSR(syst)), peak atrial longitudinal strain rate during ventricular early diastole (ALSR(early)), and peak atrial longitudinal strain rate during ventricular late diastole (ALSR(late)) compared with controls (1.73 ± 0.48 vs. 2.05 ± 0.55 1/s, -1.44 ± 0.53 vs. -2.07 ± 0.84 1/s, -2.07 ± 0.7 vs. -2.66 ± 0.91 1/s, respectively; all P<0.005). Multiple regression analysis revealed severity of gout had an independent negative impact on LA pump function (ALSR(late)). In conclusion, gout caused LV diastolic dysfunction, LV subclinical systolic dysfunction and LA reservoir, conduit, and booster pump dysfunction.